Newer versus Older Implant Systems from a Single Manufacturer and Cause-Specific Revision Risk following Primary Total Knee Arthroplasty - Kelly, Matthew P.; Prentice, Heather A.; Fasig, Brian H.; Sheth, Dhiren S.; Reddy, Nithin C.; Khatod, Monti; Paxton, Elizabeth W. (The Journal of Knee Surgery, 2025)
Novel implant systems have design modifications that seek to improve total knee arthroplasty (TKA) survivorship. We evaluated overall and cause-specific revision risk for a newer generation implant system compared with its predecessor from the same manufacturer. We conducted a cohort study using data from the United States-based Kaiser Permanente Total Joint Replacement Registry. Adult patients who underwent primary, fully cemented, fixed-bearing TKA for osteoarthritis between 2009 and 2022 were identified. Only two implant systems from the manufacturer were included: the newer generation (n = 22,287) and the older generation (n = 37,105). Multivariable Cox regression was used to evaluate overall and cause-specific aseptic revision risk. In the adjusted analyses, no difference in risk was observed for the newer compared with older generation system in the first 4-year follow-up (hazard ratio [HR] = 0.94, 95% confidence interval [CI] = 0.74–1.19); however, a higher risk was observed after 4-year follow-up (HR = 2.09, 95% CI = 1.41–3.08). This higher risk was due to loosening (within 4 years: HR = 0.90, 95% CI = 0.59–1.37; after 4 years: HR = 2.88, 95% CI = 1.84–4.51); no differences were observed for other revision reasons. When considering constructs utilizing different trays of the newer generation system, the higher risk of revision for loosening was observed only when the first iteration of the tray was used (HR = 1.94, 95% CI = 1.37–2.77); no difference was observed for constructs utilizing the subsequent iterations of the tray, which underwent design changes, when compared with the older generation TKA system (HR = 0.45, 95% CI = 0.20–1.01). We found no survivorship advantage with a newer TKA design compared with a preceding design from the same manufacturer. The higher risk of revision for loosening in the newer generation constructs was limited to those utilizing the first tray iteration, which is now discontinued by the manufacturer. The higher revision risk was not observed with subsequent iterations of the newer generation construct relative to the older generation.Level of Evidence Level III.
Keywords: total knee arthroplasty; implant generation; revision; aseptic loosening; registry